Exploration of the Fitness of Law Enforcement Candidates across Different Ethnicities - Lockie, Robert; Martin, Joel; Dawes, J. Jay; Orr, Robin; Dulla, Joseph; Sanchez, Kristine (NBP. Nauka, bezbednost, policija, 2025)
Law enforcement agencies often hire diverse candidates reflective of their community. Candidates should possess good fitness to complete academy; however, ethnicity/sociocultural norms could influence fitness. This study investigated fitness differences between law enforcement candidates of different ethnicities. Retrospective analysis was conducted on data from 2041 candidates (1659 males, 382 females) from a US law enforcement agency. During the hiring process, candidates completed: 60-s push-ups; 60-s sit-ups; 75-yard pursuit run (75PR); 60-s arm ergometer revolutions; and 2.4-km run. Candidates self-reported their ethnicity as one of the following: Asian, Black, Filipino/Pacific Islander, Hispanic, Indigenous, Non-Specified (candidate did not disclose ethnicity, ethnicity not represented in provided options), and White. A univariate analysis, with sex as a covariate, determined between-group differences (p